2020
DOI: 10.1289/ehp7201
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Metal Mixtures and Birth Weight for Gestational Age in a Predominately Lower-Income Hispanic Pregnancy Cohort in Los Angeles

Abstract: BACKGROUND: Reduced fetal growth increases the risk for adverse health outcomes. Growing evidence suggests that metal exposures contribute to reduced fetal growth, but little is known about the effects of complex metal mixtures. OBJECTIVES: We investigated the impact of a complex mixture of metals on birth weight for gestational age (BW for GA) in the Maternal and Developmental Risks from Environmental and Social Stressors study, a predominately lower-income Hispanic pregnancy cohort in Los Angeles, California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Many studies reported more than one primary effect estimate: a total of 49 results were reported across the 27 studies. A total of 33 estimates from 22 studies reported no evidence of an association [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Evidence of an inverse association between mercury and birth weight was found in 16 estimates from 11 studies [ 25 , 34 , 36 , 37 , 40 , 41 , 45 , 46 , 47 , 48 , 49 ] and possible patterns between studies that may explain these findings will be explored in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies reported more than one primary effect estimate: a total of 49 results were reported across the 27 studies. A total of 33 estimates from 22 studies reported no evidence of an association [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Evidence of an inverse association between mercury and birth weight was found in 16 estimates from 11 studies [ 25 , 34 , 36 , 37 , 40 , 41 , 45 , 46 , 47 , 48 , 49 ] and possible patterns between studies that may explain these findings will be explored in the following paragraphs.…”
Section: Resultsmentioning
confidence: 99%
“…The first group of results included investigations of mercury concentrations using whole blood or urine during the first trimester [ 28 , 35 , 37 , 41 , 49 ]. Three prospective studies of pregnancies in South Korea [ 37 ], fishing areas of the USA [ 28 ], and Los Angeles, USA [ 35 ] each found no evidence of an association with birthweight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have certainly known for decades that nutritional status can affect the toxicity of some pollutants (Mahaffey and Vanderveen 1979). Other examples of interactions between trace elements and metals related to a variety of child health outcomes also are beginning to emerge (Howe et al 2020a(Howe et al , 2020b(Howe et al , 2021Liu et al 2018). However, in many of these cases, the results suggest that the positive association between the trace element and these outcomes may be attenuated at higher levels of the toxic metal.…”
mentioning
confidence: 99%
“…We have certainly known for decades that nutritional status can affect the toxicity of some pollutants ( Mahaffey and Vanderveen 1979 ). Other examples of interactions between trace elements and metals related to a variety of child health outcomes also are beginning to emerge ( Howe et al. 2020a , 2020b , 2021 ; Liu et al.…”
mentioning
confidence: 99%